INFORMATION OF COMMUNICATION TECHNOLOGIESARE IN THE PROCESS OF FORMING OF COMPETITIVENESS OF FUTURE TEACHER OF INITIAL CLASSES - Perminova Л.А. (Journal of Information Technologies in Education (ITE), 2016)
Practice of the use of facilities of information technologies that folded in an educational process assumes their constructing during the study of any discipline of curriculum of preparation of students. The decision factor of successful introduction of information technologies in an educational process are readiness and ability of teachers to capture facilities of information technologies and to offer new methodologies with the use of these facilities. Arguments, which ground the necessity of decisions of problem of both choice and rationality of the use of information educational technologies for practice of the vocational training, are pointed in the article; the necessary pedagogical terms of their application, among which the incremental model of introduction is described in practice of teaching of future teachers of initial school, are grounded. In particular, initiation, analysis and estimation, choice of technology (or creation of authorial technology), planning of integration select technologies in an educational process, realization of project, adaptation and monitoring, estimation of realization,perspective of the use, that foresees clear control system. Grounded an author circumstance that application of computer technologies requires the revision of forms and methods of educational activity that, in turn, promotes activity, conduces to alteration of process of professional preparation taking into account the increase of level of independence of educational, cognitive activity, competitiveness of students.Supposition is pulled out in the article, that the rational use of computer technologies will permit without overloads for students, to intensify the process of their professional preparation.